Transparency and its manifestations in Russian media discourse: a case study of HC traktor - Khakimova, Elena M.; Krasavina, Anna V.; Tolstykh, Olga A. (Penerbit Universiti Kebangsaan Malaysia, 2024)
The article explores the manifestations of transparency related to the Russian political management in 2018–2019. A discursive analysis included the media materials covering the decision by Chelyabinsk (the seventh largest city in Russia) regional authorities, without public discussion, to allocate significant funds from the city budget to support HC Traktor. The public discussion of this issue was widely reflected in the media. Civic activists accessed official online documents concerning the participatory financing and initiated an online dialogue with the authorities, disagreeing with their decisions, offering alternatives, and suggesting that internal political management be made more public. The study systematizes various aspects of transparency: openness, availability, clarity, democracy, visibility and accountability. Since new media and social networks play a key role in the interaction between the state authorities and public, the paper considers all the structural elements of modern media communication: addressees, target audience, channels of information, the content and form of publications, their perlocutionary effect. The results of our study proved that communicative success was reached by breaking language standards, polycode information delivery, and storytelling techniques. The perlocutionary effect of this transparent media communication was difficult and deferred. The public dialogue did not satisfy the initial public demand, but it did influence the management practices (further reflected in Russia’s federal legislation) and accompanied changes in the composition of regional elites.